Current prevalence of Helicobacter pylori infection in patients with dyspepsia treated in Warsaw, Poland - Tacikowski, Tadeusz; Bawa, Sa’eed; Gajewska, Danuta; Myszkowska-Ryciak, Joanna; Bujko, Jacek; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction: The prevalence of Helicobacter pylori (Hp) infection in patients with dyspepsia has important clinical and epidemiological implications. However, the current prevalence of Hp infection among patients within Poland is unknown; the last data were collected a decade ago and the majority of previous studies showed the prevalence to be between 60% and 100%. Aim: To establish the current prevalence of Hp infection among patients with dyspepsia in Warsaw, Poland. Material and methods : The study group comprised 148 patients (126 women and 22 men) with dyspepsia, treated in two outpatient clinics in Warsaw. The mean age in the group that tested positive for Hp was 45.8 years (SD = 14.86; median = 51; min = 19; max = 64). They were tested for Hp infection with a urea breath test that uses 13C-enriched urea and isotope ratio mass spectrometry. Results : Hp infection was found in 53 patients (44 women and 9 men), i.e. in 35.8% of the whole study group. We did not find any significant relationship between Hp infection and the patients’ age, gender, or their body mass index. Conclusions : The current prevalence of Hp infection among patients with dyspepsia treated in Warsaw is 35.8%. However, our data suggest almost a two-fold fall in the prevalence of Hp infection compared to the previous Polish studies.